A permanência do aluno surdo no contexto universitário : desafios e estratégias - Oliveira, Keyla Aparecida Fortes de (2020)
Higher education is important in vocational training, however, the university context is a challenging phase for students, especially when it comes to deaf students. Due to disability, the deaf student faces several barriers, which can cause dropout, making the rate of deaf students graduated in higher education low. In this sense, the research conducted with undergraduate students of the Libras Degree course at the Federal University of Mato Grosso (UFMT) aimed to understand the process of insertion and path of these students and to know the strategies used for permanence. The research is inserted in the qualitative approach of descriptive character through survey of categories. Four deaf students who completed the undergraduate degree course in Letters-Libras at UFMT campus Cuiabá participated, through a semi-structured interview. Participant's ages ranged from 30 to 33 years, with the majority being female and the only deaf member in the family. The barriers faced by the deaf in the educational environment since early childhood education is an aspect that draws attention to a reflection on the inequality of opportunities in the process of insertion in higher education. The results revealed that, in general, the insertion in basic education in a regular school was perceived as a negative experience, due to the fact that they could not communicate efficiently with colleagues, teachers and managers. Different strategies were used to stay in higher education and relate to the qualification of professionals and changes in curricular practices offered by the course. Appreciation of deaf education in the academic environment is not an easy task, but it can be a step towards the personal and professional fulfillment of these subjects.